Potential Involvement of BIRC5 in Maintaining Pluripotency and Cell Differentiation of Human Stem Cells. (10th January 2019) - Gil-Kulik, Paulina; Krzyżanowski, Arkadiusz; Dudzińska, Ewa; Karwat, Jolanta; Chomik, Piotr; Świstowska, Małgorzata; Kondracka, Adrianna; Kwaśniewska, Anna; Cioch, Maria; Jojczuk, Mariusz; Nogalski, Adam; Kocki, Janusz
Abstract : The BIRC5 gene encodes a survivin protein belonging to class III of inhibitors of apoptosis, IAP. This protein serves a dual role. First, it regulates cell death, and second, it is an important regulator of mitosis progression, although its physiological regulatory function has not been fully understood. Many studies have shown and confirmed that survivin is practically absent in mature tissues in nature, while its overexpression has been reported in many cancerous tissues. There is little information about the significance of BIRC5 expression in normal adult human stem cells. This paper presents the study and analysis of survivin expression at the transcription level using qPCR method, in hematopoietic stem cells from peripheral blood mobilized with a granulocyte growth factor, adherent cells derived from the umbilical cord, and normal bone marrow stem cells. The expression of this gene was also examined in the blood of normal healthy individuals. The results of the analysis have shown that the more mature the cells are, the lower the expression of the BIRC5 gene is. The lowest expression has been found in peripheral blood cells, while the highest in normal bone marrow cells. The more the CD34+ and CD105 cells in the tested material are, the higher the BIRC5 expression is. Stem cells from cell culture show higher BIRC5 expression. The study confirms the involvement of BIRC5 from the IAP family in many physiological processes apart from apoptosis inhibition. The possible effect of BIRC5 on cell proliferation; involvement in cell cycle, cell differentiation, survival, and maintenance of stem cells; and the possible effect of IAP on the antineoplastic properties of mesenchymal stem cells have been demonstrated. Our research suggests that BIRC5 may be responsible for the condition of stem cell pluripotency and its high expression may also be responsible for the dedifferentiation of tumor cells.